Sequential maximum-likelihood estimation of wideband polynomial-phase signals on sensor array - Debre, Kaleb; Fei, Tai; Pesavento, Marius (Signal processing, 2026)
This paper presents a novel sequential estimator for the direction-of-arrival and polynomial coefficients of wideband polynomial-phase signals impinging on a sensor array. Addressing the computational challenges of maximum-likelihood estimation for this problem, we propose a method leveraging random sampling consensus (RANSAC) applied to the time-frequency spatial signatures of sources. Our approach supports multiple sources and higher-order polynomials by employing coherent array processing and sequential approximations of the maximum-likelihood cost function. We also propose a low-complexity variant that estimates source directions via angular domain random sampling. Numerical evaluations demonstrate that the proposed methods achieve Cramér-Rao bounds in challenging multi-source scenarios, including closely spaced time-frequency spatial signatures, highlighting their suitability for advanced radar signal processing applications. •FMCW radar detection of multiple targets with time-varying radial velocities.•Joint estimation of direction-of-arrival and time-frequency signatures.•Computationally tractable approximate maximum-likelihood estimation method.•Wideband space–time-frequency coherent processing.•Achieves Cramér-Rao bound for all parameters in challenging multi-source scenarios.